Explanations for the High Risk of Diabetes-Related Amputation in a Caribbean Population of Black African Descent and Potential for Prevention - Hennis, Anselm J.M.; Fraser, Henry S.; Jonnalagadda, Ramesh; Fuller, John; Chaturvedi, Nish (Diabetes care, 2004)
Explanations for the High Risk of Diabetes-Related Amputation in a Caribbean Population of Black African Descent and Potential for Prevention Anselm J.M. Hennis , MRCP, PHD 1 2 , Henry S. Fraser , FRCP, PHD 1 2 , Ramesh Jonnalagadda , MS 2 , John Fuller , FRCP 3 and Nish Chaturvedi , MRCP, MD 4 1 Chronic Disease Research Centre, Tropical Medicine Research Institute, University of the West Indies, Barbados, West Indies 2 School of Clinical Medicine & Research, University of the West Indies, Barbados, West Indies 3 University College, London, U.K. 4 National Heart & Lung Institute, Imperial College, London, U.K. Address correspondence and reprint requests to Dr. Anselm Hennis, Chronic Disease Research Centre, Tropical Medicine Research Institute, University of the West Indies, Jemmott’s Lane, Bridgetown, Barbados, West Indies. E-mail: ahennisatcaribsurf.com Abstract OBJECTIVE —Diabetes-related lower-extremity amputation (LEA) rates are elevated in blacks compared with whites in the U.S., but are lower in African Caribbeans in the U.K., whereas anecdotal reports suggest high rates in the Caribbean. We aimed to establish the incidence and risk factors for diabetes-related LEA in a Caribbean population. RESEARCH DESIGN AND METHODS —We conducted an incident and prospective case-control study of case patients (individuals with diabetes having a LEA) and community-based control subjects (individuals with diabetes without a LEA) in Barbados, West Indies. Participants completed an interview and examination of risk factors for amputation, including footwear use. RESULTS —The overall 1-year incidence of LEA ( n = 223) was 173 per 10 5 population and 936 per 10 5 population with diabetes (557 per 10 5 for minor amputation and 379 per 10 5 for major amputation). Women had higher amputation rates than those reported in the Global Lower Extremity Amputation Study, apart from the U.S. Navajo population. Independent risk factors for all diabetes-related LEAs were poor footwear (odds ratio [OR] 2.71 [95% CI 1.23–5.97]), elevated GHb (1.40 per percent increase [1.26–1.57]), peripheral neuropathy (1.05 per volt increase [1.03–1.08]), and peripheral vascular disease. CONCLUSIONS —Diabetes LEA rates in Barbados are among the highest in the world. Inadequate footwear independently tripled amputation risk. Education of professionals and patients, particularly about footwear and foot care, coupled with improved diabetes clinical care, is key to reducing amputation risk in this population. LEA, lower-extremity amputation PVD, peripheral vascular disease Footnotes A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances. Accepted August 2, 2004. Received March 11, 2004. DIABETES CARE